Distributed connectivity restoration in networks of movable sensor nodes. (November 2016) - Sharma, Krishna P.; Sharma, T.P.
Highlights: A distributed strategy is proposed for finding relocation overhead associated with movement of each node during cascaded relocation process. A criteria is given for selecting suitable node to relocate during cascaded movement. The performance of the scheme is evaluated and compared with other baseline approaches through example networks. The approach is validated analytically and through ns-2 based simulation. Abstract: In wireless sensor networks, hostile deployment terrains make resource constrained sensor nodes vulnerable to failures. Sometimes, even a single node failure can partition a network into many disjoint segments and can fail the application mission completely. Since, in most scenarios manual intervention is not possible and hence network must have self-healing capability by detecting and recovering faults at its own. In this paper, a distributed connectivity restoration (DCR) scheme is proposed which on node failure(s) reconstructs the network topology by using cascaded node movements enabling self-healing capability in the network. The DCR is based on partial network information including topological overhead associated with each node. The selection of befitting nodes to be relocated during cascaded movement is done strategically by using partial network information such that the relocation and message overheads are reduced. Ns-2 based simulation experiments are performed to evaluate the performance of the proposed scheme and is compared with other baseline approaches. Graphical abstract: